Towards restructuring the legal framework for payment system in international Islamic trade finance - Oseni, Umar Aimhanosi (Emerald Group Publishing, 2013)
Purpose – The purpose of this paper is to examine the current legal framework for payment system in international Islamic trade finance vis-à-vis the new regime introduced by the Uniform Customs and Practice for Documentary Credits (UCP) 600 as well as the Shari'ah Standard on Documentary Credits issued by the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) and Shari'ah Resolutions of selected Shari'ah Boards of Islamic financial institutions.